The Effect of Probiotic Lactobacillus acidophilus and Ethanolic Propolis Compound toward Nucleic Acid Deposition in the Extracellular Polymeric Substance of Root Canal Bacteria - Adiningrat, Arya; Kusnadi, Rifkhi A.; Allam, Asyam S.; Sofiani, Erma; Maulana, Ikhsan; Yumoto, Hiromichi (European Journal of Dentistry, 2022)
Objective This study aimed to evaluate the effects of Apis trigona ethanolic propolis and probiotic bacteria Lactobacillus acidophilus on the nucleic acid concentration in the extracellular polymeric substances (EPS) derived from biofilm of root canal bacteria.Materials and Methods Clinical bacteria of the root canal were cultured with ethanolic extract of propolis (EEP; 10 or 0.1%) and L. acidophilus. After the formation of biofilm was observed in the monolayer bacterial culture under several conditions, the enzymatic treatment and nucleic acid quantification were sequentially performed.Statistical Analysis Independent t-test and Mann–Whitney were performed following data normality to analyze the significant differences of the treatment effect on the nucleic acid concentration in EPS from the isolated biofilm.Results The results showed that the nucleic acid concentration in EPS biofilm were not increased by coculture with L. acidophilus as probiotics. However, the treatment with 10% EEP could significantly increase nucleic acid concentration.Conclusion This study suggested that the biosurfactants from probiotic bacteria L. acidophilus might be a promising candidate for endodontic treatment, arguably better than EEP in inhibiting biofilm maturation and complexity.
Keywords: ethanolic extract of propolis; extracellular polymeric substance; Lactobacillus acidophilus; extracellular nucleic acid; probiotics bacteria; root canal biofilm